Economics Education with Islamic Character Values: Fostering Frugality and Responsibility among High School Students - Rambe, Muhammad Yusuf; Tanikawa, Kanako; Siswanto, Deny Hadi (Ruang Publikasi Ilmiah, 2025)
This study aims to describe the implementation of economics learning at SMA Muhammadiyah Mlati and its impact on shaping students’ frugal behavior. The research employed a qualitative approach and was conducted August 2025, involving the principal, vice principal for curriculum affairs, economics teacher, and tenth-grade students as subjects. Primary data were obtained through observation, interviews, and documentation, while secondary data were derived from supporting documents and photographs. Data analysis followed the Miles and Huberman model, which includes the stages of data collection, reduction, presentation, and conclusion drawing. The findings reveal that economics learning was designed contextually by linking theory to real-life practices and employing interactive and motivational methods to address time constraints and student boredom. The impact of this learning process is evident in the improvement of students’ understanding of economic concepts and their application in daily life, such as saving, budgeting, and avoiding consumptive behavior. Therefore, economics learning at SMA Muhammadiyah Mlati not only enhances academic competence but also fosters Islamic character values of frugality, discipline, and responsibility.